Modeling Lake Titicaca's water balance: the dominant roles of precipitation and evaporation - Lima-Quispe, Nilo (2025)
In the face of climate change and increasing anthropogenic pressures, a reliable water balance is crucial for understanding the drivers of water level fluctuations in large lakes. However, in poorly gauged hydrosystems such as Lake Titicaca, most components of the water balance are not measured directly. Previous estimates for this lake have relied on scaling factors to close the water balance, which introduces additional uncertainty. This study presents an integrated modeling framework based on conceptual models to quantify natural hydrological processes and net irrigation consumption. It was implemented in the Water Evaluation and Planning System (WEAP) platform at a daily time step for the period 1982–2016, considering the following terms of the water balance: upstream inflows, direct precipitation and evaporation over the lake, and downstream outflows. To estimate upstream inflows, we evaluated the impact of snow and ice processes and net irrigation withdrawals on predicted streamflow and lake water levels. We also evaluated the role of heat storage change in evaporation from the lake. The results showed that the proposed modeling framework makes it possible to simulate lake water levels ranging from 3808 to 3812 m a.s.l. with good accuracy (RMSE = 0.32 m d−1) over a wide range of long-term hydroclimatic conditions. The estimated water balance of Lake Titicaca shows that upstream inflows account for 56 % (958 mm yr−1) and direct precipitation over the lake for 44 % (744 mm yr−1) of the total inflows, while 93 % (1616 mm yr−1) of the total outflows are due to evaporation and the remaining 7 % (121 mm yr−1) to downstream outflows. The water balance closure has an error of −15 mm yr−1 without applying scaling factors. Snow and ice processes, together with net irrigation withdrawals, had a minimal impact on variations in the lake water level. Thus, Lake Titicaca is primarily driven by variations in precipitation and high evaporation rates. These results will be useful for supporting decision-making in water resource management. We demonstrate that a simple representation of hydrological processes and irrigation enables accurate simulation of water levels. The proposed modeling framework could be replicated in other poorly gauged large lakes because it is relatively easy to implement, requires few data, and is computationally inexpensive.